BARRIERS TO PHYSICAL ACTIVITY IN THE ELDERLY - Paulo Matias; Raul F.2 Bartolomeu; António M. Monteiro (Federación Extremeña de Balonmano; University of Extremadura, 2015)
The population awareness of the physical exercise's benefits is widely diffused. These benefits are particularly important in the elderly because, with increasing age, there is a decline of the musculoskeletal system and the maximum oxygen consumption which reduces the functional fitness of the elderly and can often lead to a significant decline in the quality of life. Despite this awareness, a large part of the population remains sedentary. It is important to know what the barriers are, so they can be circumvented in order to increase the engagement of the elderly population in existing physical activity programs. Objectives: This study aims to identify some of the personal, behavioral and environmental barriers that prevent older adults to be physically active.